Characteristics of Physician Assistant Students Planning to Work in Primary Care: A National Study. Issue 4 (December 2019) - Larson, Eric H.; Frogner, Bianca K.
Abstract : Purpose: While the number of physician assistants (PAs) participating in the primary care workforce continues to rise, the proportion of PAs practicing in primary care rather than other specialties has decreased. The purpose of this study was to identify the characteristics of matriculating PA students planning to enter primary care specialties and compare them with students planning on entering other specialties. Methods: Data from the Physician Assistant Education Association Matriculating Student Survey (MSS) from 2013 and 2014 were analyzed. In a series of bivariate analyses, demographic characteristics, educational backgrounds, clinical experiences, and practice expectations of students intending to enter primary care practice were compared with those of their counterparts who did not intend to enter primary care. Logistic regression was used to assess the overall importance of demographic, background, and practice expectations variables on practice intentions. Results: A total of 9283 students responded to the MSS from 2013 and 2014. More than half (58.3%) stated an intention to practice in primary care upon graduation. Those students were more likely than their counterparts to be married, to be Hispanic or Asian, and to have participated in community service prior to starting PA training. They were also less likely to view high income as essential to their careers and more likely to view practicing in rural or underserved areas favorably. Conclusions: The findings of this study could be used to identify student characteristics associated with an interest in primary care and could contribute to more successful student recruitment and PA curriculum design, especially for PA training programs with a mission focused on producing primary care PAs.